Financial Burden and Mental Health Among LGBTQIA+ Adolescent and Young Adult Cancer Survivors During the COVID-19 Pandemic - Waters, Austin R.; Bybee, Sara; Warner, Echo L.; Kaddas, Heydon K.; Kent, Erin E.; Kirchhoff, Anne C. (Frontiers in Oncology, 2022)
Background In the United States, the cost of cancer treatment can lead to severe financial burden for cancer survivors. The economic impacts of the COVID-19 pandemic compound cancer survivors’ financial challenges. Financial burden may be particularly challenging for lesbian, gay, bisexual, transgender, queer, intersex, asexual and other sexual and gender minority (LGBTQIA+) survivors. LGBTQIA+ survivors who are adolescent and young adults (AYA) may face elevated financial burden due to multiple, intersecting identities. Methods An explanatory sequential mixed methods design was applied, beginning with a survey of AYA cancer survivors in the Mountain West region of the United States. Survey measures included demographics, COVID-19 impacts, the COmprehensive Score for financial Toxicity (COST), Perceived Stress Scale-4 (PSS-4), and PROMIS anxiety and depression scales. Two-way t-tests were used to analyze differences in outcomes between LGBTQIA+ and non-LGBTQIA+ AYAs. All LGBTQIA+ survey participants were invited to complete an interview, and those who agreed participated in descriptive interviews about financial burden due to cancer, COVID-19, and LGBTQIA+ identity. Interviews were audio recorded, transcribed, and analyzed using Dedoose. Results Survey participants (N=325) were LGBTQIA+ (n=29, 8.9%), primarily female (n= 197, 60.6%), non-Hispanic White (n= 267, 82.2%), and received treatment during COVID-19 (n= 174, 54.0%). LGBTQIA+ interview participants (n=9, 100%) identified as a sexual minority and (n=2, 22.2%) identified as a gender minority. Most were non-Hispanic White (n=6, 66.7%) and had received treatment during COVID-19 (n=7, 77.8%). Statistical analyses revealed that LGBTQIA+ AYAs reported significantly worse COST scores than non-LGBTQIA+ AYAs (p=0.002). LGBTQIA+ AYAs also reported significantly higher PSS-4 (p=0.001), PROMIS anxiety (p=0.002) and depression scores (p<0.001) than non-LGBTQIA+ AYAs, reflecting worse mental health outcomes. High costs of cancer treatment and employment disruptions due to COVID-19 contributed to substantial financial stress, which exacerbated existing mental health challenges and introduced new ones. Conclusions LGBTQIA+ AYA survivors reported substantial financial burden and psychological distress exacerbated by cancer, the COVID-19 pandemic, and LGBTQIA+ stigma. Given their multiple intersecting identities and potential for marginalization, LGBTQIA+ AYA survivors deserve prioritization in research to reduce financial burden and poor mental health.